1994
DOI: 10.1016/0735-1097(94)90752-8
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole directly inhibits vascular smooth muscle cell proliferation in vitro and in vivo: Implications in the treatment of restenosis after angioplasty

Abstract: Dipyridamole inhibited smooth muscle cell proliferation in vitro. This activity was attenuated by serum proteins. Locally delivered dipyridamole inhibited cell replication in arteries and intimal thickening after balloon injury. These results suggest that although systemic treatment with dipyridamole may not be efficacious because of inadequate serum levels, its antiproliferative action on smooth muscle cells may reduce restenosis when the drug is delivered locally after coronary angioplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…The non-thrombogenicity and the antiproliferative ability are dependent on the DPA dose according to a previous report [23]. DPA was locally delivered into a rabbit model with carotid or femoral artery injury, and exhibited a dose-dependent inhibition of SMC proliferation [21]. In this study, the dose dependence was not distinct in non-thrombogenicity, whereas it was shown in HASMC proliferation inhibition.…”
Section: Discussionmentioning
confidence: 61%
“…The non-thrombogenicity and the antiproliferative ability are dependent on the DPA dose according to a previous report [23]. DPA was locally delivered into a rabbit model with carotid or femoral artery injury, and exhibited a dose-dependent inhibition of SMC proliferation [21]. In this study, the dose dependence was not distinct in non-thrombogenicity, whereas it was shown in HASMC proliferation inhibition.…”
Section: Discussionmentioning
confidence: 61%
“…A number of drugs have been shown to inhibit the growth of vascular smooth muscle cells (e.g., heparin [18], calcium channel blockers [19], angiotensin-converting enzyme inhibitors [20], dipyridamole [21,22], and paclitaxel [11,12]). Attempts to reduce vascular stenosis in various animal models by the systemic administration of these agents have been largely unsuccessful.…”
Section: Discussionmentioning
confidence: 99%
“…A large multicenter trial sponsored by the National Institutes of Health using the oral combination of dipyridamole and aspirin in preventing AV graft failure in dialysis patients is ongoing. Continuous adventitial dipyridamole delivery using an osmotic pump inhibited NH formation in rabbit artery-injury models 202. In contrast, there was no significant decrease in restenosis rates after coronary angioplasty using intracoronary dipyridamole in a small randomized clinical trial 203.…”
Section: Prevention Strategiesmentioning
confidence: 99%